The main determinants of green competitiveness - Lyulyova, Lilia; Saenko, Marina (Вісник Економіки, 2020)
Introduction. The development of the business sector is characterized by the tendency of many enterprises to promote environmentally friendly strategies, implement sustainable development goals, which will help solve global and local environmental problems, reduce anthropogenic pressure on the environment, save resources, form competitive development of the country and business sector as a whole.The purpose of the article is to study scientific approaches to determining the main factors and components of sustainable competitiveness, defining key goals (target groups) and determinants that will determine the subject basis of appropriate marketing strategies to ensure the green competitiveness of enterprises.Results. In order to form strategic guidelines for promoting green competitiveness, the article has systematized scientific approaches to its research, which include marketing, technology, innovation, communication, stakeholder, quality, level, financial and ethical areas.The authors have emphasized that the processes of providing environmentally friendly competitive advantages are largely determined by a set of appropriate determinants. The article proposes to create two groups of the relevant determinants, which will be determined by objective (external) and subjective (internal) components. The system of relevant factors is proposed to be classified according to managerial, financial, infrastructural, nanoeconomics, behavioral, production, innovation, and cultural and ethical criteria. The content of external and internal determinants is determined for each criterion separately.Prospects for further research. The study of the main determinants of green competitiveness will form a range of appropriate strategies for its promotion. It is advisable to use these components as key guidelines, primarily related to internal components.Keywords: sustainable development; green competitiveness; determinants; strategies; innovation.Вступ. Розвиток підприємницького сектору характеризуються схильністю багатьох підприємств до просування екологічно орієнтованих стратегій функціонування, реалізації виконання цілей сталого розвитку, що буде сприяти розв’язанню глобальних та локальних екологічних проблем, зниженню антропогенного навантаження на довкілля, економії ресурсів, формуваннюконкурентоспроможного розвитку країн та підприємницького сектору в цілому.Метою статті є вивчення наукових підходів до визначення основних факторів та компонентів стійкої конкурентоспроможності, визначення ключових цілей (цільових груп) та детермінант, які визначать предметну основу відповідних маркетингових стратегій для забезпечення зеленої конкурентоспроможності підприємств.Результати. З метою формування стратегічних орієнтирів просування зеленої конкурентоспроможності в статті систематизовано наукові підходи до її дослідження, які включають маркетингові, технологічні, інноваційні, комунікаційні, стейкхолдерські, якісні, рівневі, фінансові та етичні напрямки.Автори підкреслюють, що процеси забезпечення екологічно орієнтованих конкурентних переваг багато в чому визначаються набором відповідних детермінант. В статті запропоновано групувати відповідні детермінанти на дві групи, які будуть визначатися об’єктивними (зовнішніми) та суб’єктивними (внутрішніми) компонентами. Систему відповідних факторів запропоновано класифікувати за управлінськими, фінансовими, інфраструктурними, наноекономічними, поведінковими, виробничими, інноваційними та культурно- етичними критеріями. При цьому зміст екстернальних та інтернальних детермінант визначається для кожного критерію окремо.Перспективи подальших досліджень. Дослідження головних детермінант зеленої конкурентоспроможності буде формувати коло відповідних стратегій її просування. В якості ключових орієнтирів доцільно використовувати зазначені складові, пов’язані, в першу чергу, з інтернальними складовими.Ключові слова: сталий розвиток; зелена конкурентоспроможність; детермінанти; стратегії; інновації.